Ab Initio Study of the Raman Spectra of Amorphous Oxides: Insights into the Boson Peak Nature in Glassy TeO2. Issue 4 (5th April 2023) - Roginskii, Evgenii M.; Raghvender, Raghvender; Noguera, Olivier; Thomas, Philippe; Masson, Olivier; Bouzid, Assil
Abstract : Amorphous Oxides By relying on density functional perturbation theory and finite difference method, in article number 2200505, Evgenii M. Roginskii, Assil Bouzid, and co‐workers compute Raman spectra on large atomistic models of amorphous oxide systems in close comparison to experiments. Thanks to the analysis of the normal modes of vibrations, the authors discuss the origins of the Boson peak and correlate it to collective vibrations of the main structural units of the glass.